Pavlova cake bakery / Farra Natasya Abdullah, Hasya Umairah Halem and Ku Ahmad Akif Ku Harmi - Abdullah, Farra Natasya; Halem, Farra Natasya; Ku Harmi, Ku Harmi (2023)
Pavlova Cake Bakery is a company that creates sponge cake with pavlova placed on top to plunge our creativity into the consumers’ wants. Each of the task conducted in the dessert business are solely manage by our team members who act as the managers in each of their particular field area in the starting of the first year. This action could help us to heavily focus on strengths and weaknesses during the process while to overcome the shortcomings that our part lacks in order to expand our growth with the guidance of Malaysia’s funding organization such as TEKUN that proves to provide assistance in terms loaning purpose. To produce our masterpiece, we only purchase the ingredients at its newest state that being the main reason for our business to flourish with wonderful recipes. We have extended our company’s business by publishing our products through online marketing by having the public to easily purchase from personalised shopping blog including online database and Grab app specifically. Strategic connection proximity such as high school and hospital nearby serves as a leaping stone for future business openings or as a hotspot location for bulk pre-order to surface. Our pure hearted intention is to provide everyone with the freshest product that comes with reasonable and affordable price. Those are the reason for the high sales revenue could be obtained from since our product’s demographic and target market are relevant for them to learn more about us which includes children, teens and people of all ages. The expenses and momentum established with the public are reduced when we use the proper distribution channels